PENERAPAN LEARNING ORGANIZATION PADA INSTITUSI PUBLIK (STUDI DI KELURAHAN SAGO KECAMATAN SENAPELAN KOTA PEKANBARU) - Suci Rahmadani; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The purpose of this study was to find out and analyze the application of learning organizations in Sago Village and find out the factors that support the implementation of learning organizations in Sago Village. This study is a type of descriptive qualitative research with a case study approach using a theory from Peter M. Senge. Data extraction techniques used were interviews with 8 key informants and 5 supporting informants in Sago Village. Data collection was also collected by good document study techniques and observations. Organizational learning is measured from the same three levels, namely individuals, groups and organizations. Senge proposed 5 disciplines to find out the application of learning organizations in an organization, personal mastery, mental models, shared vision, team learning and systems thinking. The results of the research show that the five disciplines put forward by Senge have been applied quite well in Sago Village. The implementation of learning organizations in Sago Village is supported by leadership and collaboration between employees. There are several obstacles in implementing learning organizations such as the lack of tools for employees to study and time that does not remain an obstacle for employees and people who have different activities. Keywords: Organizational learning, leadership, collaboration